Cross‐Border Knowledge Transfer in the Digital Age: The Final Curtain Call for Long‐Term International Assignments? - Bucher, Jana; Bader, Benjamin; Deller, Jürgen (Journal of Management Studies, 2024)
AbstractDigital technology has altered how multinational companies (MNCs) transfer knowledge across borders. With digital communication media (DCM), knowledge exchange can become more cost‐effective, thereby reducing the need for face‐to‐face exchange. DCM's influence on long‐term international assignment management for cross‐border knowledge transfer remains unclear. Based on 71 interviews with German human resource (HR) managers and subsidiary HR counterparts, we investigated the use of DCM to exchange knowledge across country borders. Exploring these conditions alongside HR managers’ unique perspective on global mobility management prior to and during the global COVID‐19 pandemic, we present two major findings. First, 12 facilitating conditions are necessary for digital knowledge transfer across borders to be accepted as a valuable alternative to long‐term international assignments. Second, we identified individual connections between facilitating conditions and found that five conditions decreased in relevance, while the remaining seven became core aspects of successful digital knowledge transfer during COVID‐19 and possibly beyond.